Synthesis of a fused N-bridged (3.3.1)nonadiquinoline multicyclic skeleton via a metal-free formal (4 + 2) cycloaddition/Mannich/dearomatization domino reaction - Amiri, Kamran; Nayebzadeh, Behrouz; Kamangar, Mohammad; Babazadeh, Mohammad; Ariafard, Alireza; Shiri, Farshad; Rominger, Frank; Balalaie, Saeed (Green chemistry, 2023)
We present a novel green synthetic protocol for the construction of a broad range of substituted fused azabicyclo[3.3.1]nonadiquinoline scaffolds through a formic acid catalyzed formal [4 + 2] annulation/Mannich/dearomatization domino reaction. This unified strategy shows a broad substrate scope with high functional group tolerance, resulting in good to high yields under environmentally benign, transition-metal-free, low-cost, and operationally simple conditions. The current method outperforms existing methods in terms of green and sustainable conditions. The reaction mechanism was confirmed based on DFT calculations.
Online veröffentlicht: 29. September 2023
Gesehen am 04.01.2024
Der Ausdruck "3.3.1" sowie der Ausdruck "4 + 2" sind im Titel eckig geklammert